Dressing for the weather - Harper, Kathryn, 1979-; Sims, Sean (Cambridge, U.K. : Cambridge University Press, 2016)
Looks at how people from all over the world dress in order to protect themselves from the weather.
"UCL, Institute of Education."
Includes index.
1.7
K-3
K-3
Keywords: Clothing and dress -- Juvenile literature; Weather -- Social aspects -- Juvenile literature; Clothing and dress; Weather; Weather -- Social aspects; Clothing and dress; Weather; Weather -- Social aspects; Readers (Publications)